ENVIRONMENTAL AWARENESS IN ELT: A CRITICAL DISCOURSE ANALYSIS OF THE ENGLISH FOR NUSANTARA GRADE IX TEXTBOOK - Sahmiral Amri Rajagukguk (Universitas Negeri Islam Sumatera Utara, 2025)
Environmental awareness has become an important goal in education as global environmental problems continue to increase. In English Language Teaching (ELT), textbooks play a key role in shaping students' understanding of sustainability and their attitudes toward nature. However, many textbooks present environmental issues only as moral lessons without encouraging critical thinking. This study aims to investigate how environmental awareness is represented in the Indonesian ELT textbook English for Nusantara for Grade IX. The research applies a qualitative design using Critical Discourse Analysis (CDA) and ecolinguistic perspectives based on Fairclough's three-dimensional model. The analysis includes both textual and visual data from three selected chapters that discuss wildlife conservation, environmental ethics, and upcycling. The findings show that the textbook uses eco-lexicons and positive imagery to promote empathy for nature but frames environmental responsibility mostly as individual action rather than collective or structural change. The study concludes that while the textbook encourages positive behavior and care for the environment, it still lacks critical eco-literacy that empowers students to question broader environmental and social issues.